Penentuan Kurva Pertumbuhan Lactococcus lactis dan Evaluasi Potensi Supernatan Bebas Sel sebagai Agen Antibakteri terhadap Escherichia coli - Krista, Gustin Mustika; Rinaldi, Kardian; Rahma, Andien Tiara; Maswanti, Azzahra Junisa (Politeknik Negeri Lhokseumawe, 2025)
The increasing resistance of pathogenic bacteria to synthetic antibiotics has driven the search for safer and more sustainable natural antimicrobial agents. Lactic acid bacteria, particularly Lactococcus lactis, are known to produce bioactive compounds such as bacteriocins that can inhibit the growth of pathogenic microorganisms. This study aimed to evaluate the growth profile of L. lactis, its antibacterial activity against Escherichia coli, and to identify functional groups of active compounds using Fourier Transform Infrared (FTIR) spectroscopy. Antibacterial activity was assessed using the disk diffusion method on MHA plates inoculated with standardized E. coli suspensions. The growth curve analysis showed that L. lactis entered the lag phase between 0–9 hours, the logarithmic phase from 10–17 hours, and the stationary phase from 18–40 hours. The highest antibacterial activity was observed at 23 hours of incubation, with an inhibition zone diameter of 20 mm against E. coli. FTIR analysis of the cell-free supernatant revealed the presence of O–H, C–H, amide I, COO⁻, and C–O functional groups, suggesting the presence of bioactive compounds such as bacteriocins (e.g., nisin), lactic acid, and carbohydrate residues from the fermentation medium. These findings highlight the potential of L. lactis as a natural antimicrobial agent and support its further application in functional food development and biopharmaceutical formulations.